The Impact of Digital Literacy and E-Commerce Utilization on Horticultural Farmers’ Production Decisions in Kulon Progo Regency - Pancar Topodriyo; Agus Tri Basuki; Ahmad Ma'ruf (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how digital literacy and e-commerce utilization influence production decisions among horticultural farmers in Kulon Progo Regency. It aims to analyze the partial and simultaneous effects of both variables on farmers’ production decisions. The study employed a quantitative approach using survey data collected through Likert-scale questionnaires and analyzed with multiple linear regression. The results show that digital literacy and e-commerce utilization have positive and significant effects, both individually and simultaneously, on production decisions. These findings imply that strengthening farmers’ digital capacity and market access may support more effective and adaptive agricultural decision-making. Keywords: Digital Literacy; E-Commerce Utilization; Production Decisions; Horticultural Farmers; Agricultural Marketing; Farmer Behavior